The Egyptian mummies and coffins of the Denver Museum of Nature & Science : history, technical analysis, and conservation - Koons, Michele L.; MacLeod, Caroline Arbuckle (University Press of Colorado, 2021)
"In the 1980s, Denver Museum of Nature & Science acquired two ancient Egyptian mummies and coffins. The mummies are from an unknown locale and have been subject of unpublished scientific and unscientific analyses. The DMNS staff scientists decided to reexamine the mummies and coffins using new and innovative techniques"--